INFLUENCE OF IRRADIATION ON POWDER CHARACTERISTICS AND CHITOSAN SOLUTION (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Chitosan is a biodegradable polymer composed of β- (1,4) -D-glucosamine linkages (deacetylated unit) and N- acetyl-D-glucosamine (acetylated  unit).  It is commercially produced  by the deacetylation  of chitin  and in  the food industries it is used as a stabilizer, thickener, in water treatment and easily processed into nanofibers, gels, nanoparticles  and  films.  The  objective  of  this  work  was  to  evaluate  the  effect  of  gamma  irradiation  on morphological, rheological and color properties of chitosan and gels. Chitosan samples were irradiated at the 5, 10  and  15  kGy  doses  and  performed  by  scanning  electron  microscopy  (SEM),  color  and  rheology.  SEM analyzes showed that the chitosan particles have a network agglomerated with irregular arrangements, and the irradiated  samples  presented  smaller  granules.  It  was  observed  that  gamma radiation  induces  changes  in the intensity of the tonality of the chitosan   powder   and gels, increasing the brown   coloration. These changes are  observed    by    the    decreasing    values    of    L  *    (luminosity)    with    increasing    radiation    dose    and, consequently,  an increase  in  the  values  of  b  *  (brown  tone),  C  *  and  h  *,  indicating  a  higher  intensity of   color. As   for  the rheological   behavior,  all   the  gels   were   characterized   as   Newtonian   fluids   and   the irradiation  altered  their viscosity, leaving them less viscous.